Composite insulator umbrella skirt material aging degree characterization method and system based on surface cracking degree
By using a method based on the degree of surface cracking, the surface crack characteristics of composite insulator umbrella skirt materials under different tensile strain values were collected, and the aging degree index was calculated, which solved the problem of insufficient aging degree evaluation in the prior art, and achieved fine distinction and precise characterization of the aging degree of composite insulator materials.
Patent Information
- Application Number
- CN202411914246.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, the aging degree characterization method of composite insulator umbrella skirt materials is greatly affected by the test conditions, the number of grading is limited, and the changes in the material structure are not fully considered, resulting in the inadequate evaluation of the aging degree.
Using a method based on the degree of surface cracking, the surface cracking characteristics of the sample to be tested under different tensile strain values were collected, and the aging degree index was calculated, and the aging degree of composite insulator umbrella skirt material was judged.
This method can more accurately reflect the true aging state of the material, realize fine distinction and precise characterization of the aging degree of composite insulator materials, and avoid the impact of test conditions and surface cleanliness on the results.
Smart Images

Figure CN119643290A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite insulator performance detection, and in particular relates to a method and system for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking. Background Art
[0002] Transmission lines are channels for power transmission and the guarantee of people's lives and economic development. The safe and reliable operation of transmission lines is of vital importance. If their insulation fails, it will cause great safety risks and social harm. Transmission line insulators are an important form of insulation for transmission lines. For a long time, composite insulators have been widely used in transmission lines of various voltage levels due to their excellent anti-fouling, good insulation performance and good economy.
[0003] During operation, composite insulators are subjected to harsh working conditions, such as high temperature, high temperature difference, radiation, high electric field, smoke, moisture, chemical corrosion, bird damage, etc. This causes the shed, the key part of the composite insulator, to age, specifically the silicone rubber material of the shed undergoing structural evolution and macro-performance degradation. When aging is severe, cracks will occur on the surface of the shed material, and cracks will form. The corresponding macro-performance is manifested in high leakage current, decreased hydrophobicity, reduced surface flashover voltage, and changes in mechanical properties. It can be seen that understanding the aging law of composite insulator shed materials and accurately extracting their aging degree are of great significance to ensuring the safe and stable operation of the power grid.
[0004] In the prior art, the methods for characterizing the aging degree of composite insulator shed materials include water spray classification method, contact angle test, leakage current, surface flashover voltage, etc. These methods for characterizing the aging degree of composite insulator materials have their own characteristics, but the data obtained by these methods are greatly affected by the test conditions. For example, the surface cleanliness will affect these tests. At the same time, the number of classifications for the aging degree of shed materials based on the data of these methods is limited. For example, the water spray classification method often has 7 levels, which may lead to the inability to accurately and meticulously reflect the aging degree of shed materials.
[0005] In order to solve the above technical problems, the present invention provides a method and system for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking. Summary of the invention
[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a method and system for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking. The cracks focused on by the present invention are structural changes that occur when the shed material is aged to a certain extent. The aging degree of the shed material can be understood more accurately from the perspective of its structural evolution ability. Therefore, the resolution of the aging degree is higher, and the aging degree of the composite insulator material can be finely distinguished.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking, comprising: Collect the surface crack characteristics of the sample under different tensile strains; Calculate the aging index based on the collected surface crack characteristics; The aging degree of the composite insulator shed material is judged based on the aging degree index.
[0008] Preferably, the surface crack characteristics include the total length of the cracks, the width between the cracks, and the irregularity of the cracks; The total length of cracks refers to the total length of all cracks within a certain field of view; the width between cracks refers to the width between adjacent cracks; and the irregularity of cracks refers to the degree to which cracks deviate from a straight line.
[0009] Preferably, the specific process of collecting the surface crack characteristics of the sample to be tested under different tensile strain amounts is as follows: Observe the surface crack morphology of the sample under different tensile strains and record pictures; Grayscale Figure 2 The image is processed by binarization, and the total number of pixels of cracks within a certain field of view is counted based on binarization to obtain the total length L of the cracks. The width is calculated by the ratio of a fixed straight-line distance and the number of cracks intersecting within a fixed straight-line distance. The average value of multiple calculations is taken to obtain the width d between cracks. The irregularity s of the cracks is calculated by the ratio of the total length of a single crack within a fixed straight-line distance to the straight-line distance, and the surface crack characteristics of the sample to be tested under different tensile strains are collected.
[0010] Preferably, the calculation formula for calculating the aging degree index based on the collected surface crack characteristics is as follows: ; Among them, IR is the aging degree index; I (n+1)~n is the index of crack degree variation; L is the total length of cracks; d is the width between cracks; s is the irregularity of cracks; ω s The weight coefficient of the irregularity of the crack is 0.10~0.70; ω L is the weight coefficient of the total length of the crack, ranging from 0.4 to 0.95; ω dis the weight coefficient of the crack width, ranging from 0.15 to 0.80; n is the nth tensile test, n+1 is the n+1th tensile test, and the strain of the n+1th tensile test needs to be greater than the strain of the nth tensile test; m is the number of tensile tests, and m should be greater than or equal to 2; a n is the strain of the nth tensile test; x n is the correction coefficient corresponding to the strain of the nth tensile test.
[0011] Preferably, the aging degree index is proportional to the change in the surface crack characteristics under different tensile strain amounts, and the aging degree is proportional to the aging degree index; Among them, the changes in surface crack characteristics include the changes in the total length of the cracks, the changes in the irregularity of the cracks, and the changes in the width between the cracks.
[0012] The present invention also provides a composite insulator shed material aging degree characterization system based on the surface cracking degree, comprising: A collection module, used to collect surface crack characteristics of the sample under different tensile strains; A calculation module, used to calculate an aging degree index based on the collected surface crack characteristics; The judgment module is used to judge the aging degree of the composite insulator shed material based on the aging degree index.
[0013] Preferably, the surface crack features in the acquisition module include the total length of the cracks, the width between the cracks, and the irregularity of the cracks; The total length of cracks refers to the total length of all cracks within a certain field of view; the width between cracks refers to the width between adjacent cracks; and the irregularity of cracks refers to the degree to which cracks deviate from a straight line.
[0014] Preferably, the acquisition module is specifically used to acquire the surface crack characteristics of the sample to be tested under different tensile strain amounts in the following manner: Observe the surface crack morphology of the sample under different tensile strains and record pictures; Grayscale Figure 2 The image is processed by binarization, and the total number of pixels of cracks within a certain field of view is counted based on binarization to obtain the total length L of the cracks. The width is calculated by the ratio of a fixed straight-line distance and the number of cracks intersecting within a fixed straight-line distance. The average value of multiple calculations is taken to obtain the width d between cracks. The irregularity s of the cracks is calculated by the ratio of the total length of a single crack within a fixed straight-line distance to the straight-line distance, and the surface crack characteristics of the sample to be tested under different tensile strains are collected.
[0015] Preferably, the calculation module is specifically used to calculate the aging degree index according to the collected surface crack characteristics in the following manner: ; Among them, IR is the aging degree index; I (n+1)~n is the index of crack degree variation; L is the total length of cracks; d is the width between cracks; s is the irregularity of cracks; ω s The weight coefficient of the irregularity of the crack is 0.10~0.70; ω L is the weight coefficient of the total length of the crack, ranging from 0.4 to 0.95; ω d is the weight coefficient of the crack width, ranging from 0.15 to 0.80; n is the nth tensile test, n+1 is the n+1th tensile test, and the strain of the n+1th tensile test needs to be greater than the strain of the nth tensile test; m is the number of tensile tests, and m should be greater than or equal to 2; a n is the strain of the nth tensile test; x n is the correction coefficient corresponding to the strain of the nth tensile test.
[0016] Preferably, the aging degree index configured in the judgment module is proportional to the change in surface crack characteristics under different tensile strain amounts, and the aging degree is proportional to the aging degree index; wherein the change in surface crack characteristics includes the change in the total length of the cracks, the change in the irregularity of the cracks, and the change in the width between the cracks.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking, which can finely evaluate the aging degree of composite insulator materials. The reasons are: first, compared with other methods, the cracks that this characterization method focuses on are the surface structural characteristics of the insulator shed materials themselves, and their characterization is not affected by surface cleanliness and test conditions. Secondly, the shed materials are subjected to different aging effects under different service conditions of the insulators, and will present different crack characteristics. The evolution speed of cracks in shed materials with a high degree of aging is often faster, and the strain generated during stretching can promote the evolution of cracks, so that the aging degree of the shed materials can be characterized by changes in crack characteristics. Evaluating the aging degree of composite insulator shed materials based on changes in cracks effectively solves the technical problems in the prior art that are greatly affected by test conditions, have limited aging degree grading, and lack evaluation from the perspective of structural evolution.
[0018] Furthermore, the present invention evaluates the aging degree of the material by observing and analyzing the crack characteristics (including the total length of the cracks, the width between the cracks, and the irregularity of the cracks) of the composite insulator shed material under different tensile strains. The cracks are an important structural change in the material aging process. Evaluating the aging degree from the perspective of the surface structure can more accurately reflect the actual aging state of the material.
[0019] Furthermore, the present invention calculates an aging index (IR), which comprehensively considers multiple factors such as the total length of cracks, the width between cracks, and the irregularity of cracks, as well as their changes under different tensile strains. Since the aging index is proportional to the change in the above-mentioned surface crack characteristics, it can more finely distinguish the aging degree of the composite insulator material, thereby achieving accurate characterization of the aging degree. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of a method for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking of the present invention; Figure 2 It is a schematic diagram of the system for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking of the present invention. DETAILED DESCRIPTION
[0021] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0022] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0023] In the prior art, the data obtained by existing characterization methods (such as water spray classification method, contact angle test, leakage current, surface flashover voltage, etc.) are greatly affected by the test conditions. For example, external factors such as surface cleanliness will have a significant impact on these test results, which may lead to misjudgment of the degree of aging.
[0024] The number of classifications is limited. The number of classifications for the aging degree of shed materials based on the data of existing methods is limited. For example, the water spray classification method can usually only be divided into 7 levels. This limited number of classifications may not accurately reflect the actual situation of material aging, especially when the aging degree is similar, it is difficult to make a fine distinction.
[0025] Insufficient consideration of structural changes. Existing characterization methods may not fully consider the structural changes that occur in shed materials during aging, such as cracks and cracks. These structural changes are important characteristics of shed materials when they age to a certain extent. Understanding their aging degree from the perspective of the material's structural evolution ability may be more accurate and can achieve higher-resolution aging degree differentiation.
[0026] In view of the technical problems existing in the above-mentioned prior art, the present invention provides a method for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking.
[0027] The present invention is further described in detail below in conjunction with the accompanying drawings: See also Figure 1 This embodiment provides a method for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking, comprising the following steps: S1: Collect the surface crack characteristics of the sample under different tensile strains; S2: Calculate the aging index based on the collected surface crack characteristics; S3: Determine the aging degree of the composite insulator shed material based on the aging degree index.
[0028] In one embodiment, the surface crack characteristics include the total length of the cracks, the width between the cracks, and the irregularity of the cracks; Among them, the total length of cracks refers to the total length of all cracks within a certain field of view; the width between cracks refers to the width between adjacent cracks; and the irregularity of cracks refers to the degree to which the cracks deviate from a straight line.
[0029] In one embodiment, the specific process of collecting the surface crack characteristics of the sample under different tensile strains is as follows: Observe the surface crack morphology of the sample under different tensile strains and record pictures; Grayscale Figure 2The image is processed by binarization, and the total number of pixels of cracks within a certain field of view is counted based on binarization to obtain the total length L of the cracks. The width is calculated by the ratio of a fixed straight-line distance and the number of cracks intersecting within a fixed straight-line distance. The average value of multiple calculations is taken to obtain the width d between cracks. The irregularity s of the cracks is calculated by the ratio of the total length of a single crack within a fixed straight-line distance to the straight-line distance, and the surface crack characteristics of the sample to be tested under different tensile strains are collected.
[0030] In one embodiment, the calculation formula for calculating the aging degree index based on the collected surface crack characteristics is as follows: ; Among them, IR is the aging degree index; I (n+1)~n is the index of crack degree variation; L is the total length of cracks; d is the width between cracks; s is the irregularity of cracks; ω s The weight coefficient of the irregularity of the crack is 0.10~0.70; ω L is the weight coefficient of the total length of the crack, ranging from 0.4 to 0.95; ω d is the weight coefficient of the crack width, ranging from 0.15 to 0.80; n is the nth tensile test, n+1 is the n+1th tensile test, and the strain of the n+1th tensile test needs to be greater than the strain of the nth tensile test; m is the number of tensile tests, and m should be greater than or equal to 2; a n is the strain of the nth tensile test; x n is the correction coefficient corresponding to the strain of the nth tensile test.
[0031] The above-mentioned aging degree index is proportional to the change of surface crack characteristics under different tensile strain amounts, and the aging degree is proportional to the aging degree index, wherein the change of surface crack characteristics includes the change of the total length of cracks, the change of irregularity of cracks and the change of width between cracks.
[0032] In a specific embodiment, a method for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking includes the following steps: Step 1: extract and collect the surface crack characteristics of the sample under different tensile strains; wherein the surface crack characteristics include the total length of the cracks, the width between the cracks, and the irregularity of the cracks; Step 2: Calculate the aging index according to the surface crack characteristics of the sample under different tensile strains; Step 3: Determine the aging degree of the composite insulator shed material based on the aging degree index.
[0033] Before the above step 1, the sample to be tested is processed and tested as follows: The sheds of composite insulators were selected to prepare test samples, and mechanical tensile tests were carried out on the test samples.
[0034] The specific process is as follows: Take samples from the shed of the composite insulator to prepare strip samples or dumbbell samples; The strip sample or dumbbell sample is ultrasonically cleaned with anhydrous ethanol and distilled water in turn to complete the preparation of the sample to be tested; The two ends of the sample to be tested are stretched in opposite directions to a certain tensile strain, the tensile strain is recorded, and the stretching time is maintained.
[0035] Among them, the shape of the sample to be tested is strip or dumbbell-shaped, one side of the sample to be tested needs to be the upper surface or lower surface of the umbrella skirt, and the long side of the strip sample or dumbbell-shaped sample should be along the radius direction of the umbrella skirt or perpendicular to the radius direction of the umbrella skirt.
[0036] The samples to be tested are taken from different sheds of the insulator string, including the high-voltage end shed, the low-voltage end shed, and the middle shed; the samples to be tested are taken from different positions of the shed, including the upper surface and the lower surface, the inner side of the shed, and the outer side of the shed.
[0037] The preparation of the sample to be tested includes cleaning the dirt on the sample surface, that is, placing the sample in anhydrous ethanol for ultrasonic cleaning, and then placing it in distilled water for ultrasonic cleaning; avoiding damaging the sample surface during sample preparation. In the sample preparation stage, the present invention adopts the steps of ultrasonic cleaning with anhydrous ethanol and distilled water to ensure the cleanliness of the sample surface, thereby reducing the influence of the surface cleanliness on the test results.
[0038] When carrying out the above-mentioned tensile test, it can be completed under different temperature environments to obtain the crack morphology characteristics and corresponding stress and strain of silicone rubber materials at different temperatures. The strain range of the sample, that is, the sample size increment range is 3%~50%; the stretching time range is 1s~100h; the test temperature range is -50℃~300℃.
[0039] The specific process of extracting and collecting the surface crack characteristics of the sample under different tensile strains in step 1 is as follows: Observe the surface of one side of the sample to be tested, which corresponds to the upper surface or lower surface of the shed, and observe the surface crack morphology of the sample to be tested under different tensile strains and record pictures; Grayscale Figure 2The image is processed by binarization, and the total number of pixels of cracks within a certain field of view is counted based on binarization to obtain the total length L of the cracks. The width is calculated by the ratio of a fixed straight-line distance and the number of cracks intersecting within a fixed straight-line distance. The average value of multiple calculations is taken to obtain the width d between cracks. The irregularity s of the cracks is calculated by the ratio of the total length of a single crack within a fixed straight-line distance to the straight-line distance, and the surface crack characteristics of the sample to be tested under different tensile strains are collected.
[0040] The above-mentioned surface crack characteristics include the total length of cracks, the width between cracks, and the irregularity of cracks; the total length of cracks refers to the total length of all cracks within a certain field of view; the width between cracks refers to the width between adjacent cracks; the irregularity of cracks refers to the degree to which the cracks deviate from a straight line. The above-mentioned surface crack characteristics can reflect the morphological characteristics.
[0041] In step three, the method for determining the degree of aging is that the degree of aging is proportional to the aging degree index, proportional to the change in the total length of the cracks under different strains, proportional to the change in the irregularity of the cracks, and proportional to the change in the width between the cracks.
[0042] See also Figure 2 This embodiment also provides a composite insulator shed material aging degree characterization system based on the surface cracking degree, including: A collection module, used to collect surface crack characteristics of the sample under different tensile strains; A calculation module, used to calculate an aging degree index based on the collected surface crack characteristics; The judgment module is used to judge the aging degree of the composite insulator shed material based on the aging degree index.
[0043] In one embodiment, the surface crack features in the acquisition module include the total length of cracks, the width between cracks, and the irregularity of cracks; the total length of cracks refers to the total length of all cracks within a certain field of view; the width between cracks refers to the width between adjacent cracks; the irregularity of cracks refers to the degree to which cracks deviate from a straight line.
[0044] In one embodiment, the acquisition module is specifically used to acquire the surface crack characteristics of the sample under different tensile strains in the following manner: Observe the surface crack morphology of the sample under different tensile strains and record pictures; Grayscale Figure 2The image is processed by binarization, and the total number of pixels of cracks within a certain field of view is counted based on binarization to obtain the total length L of the cracks. The width is calculated by the ratio of a fixed straight-line distance and the number of cracks intersecting within a fixed straight-line distance. The average value of multiple calculations is taken to obtain the width d between cracks. The irregularity s of the cracks is calculated by the ratio of the total length of a single crack within a fixed straight-line distance to the straight-line distance, and the surface crack characteristics of the sample to be tested under different tensile strains are collected.
[0045] In one embodiment, the calculation module is specifically used to calculate the aging index according to the collected surface crack characteristics in the following manner: ; Among them, IR is the aging degree index; I (n+1)~n is the index of crack degree variation; L is the total length of cracks; d is the width between cracks; s is the irregularity of cracks; ω s The weight coefficient of the irregularity of the crack is 0.10~0.70; ω L is the weight coefficient of the total length of the crack, ranging from 0.4 to 0.95; ω d is the weight coefficient of the crack width, ranging from 0.15 to 0.80; n is the nth tensile test, n+1 is the n+1th tensile test, and the strain of the n+1th tensile test needs to be greater than the strain of the nth tensile test; m is the number of tensile tests, and m should be greater than or equal to 2; a n is the strain of the nth tensile test; x n is the correction coefficient corresponding to the strain of the nth tensile test.
[0046] The aging degree index configured in the judgment module is proportional to the change in surface crack characteristics under different tensile strain amounts, and the aging degree is proportional to the aging degree index; wherein the change in surface crack characteristics includes the change in the total length of cracks, the change in the irregularity of cracks, and the change in the width between cracks.
[0047] Example 1 Silicone rubber material was obtained from the shed of a composite insulator that had been in service for 6 years. The shed was selected from the high-voltage end shed, and three strip samples were prepared (the surface of the sample included the upper surface of the shed), and the sample names were A, A-1, and A-2. The strip samples were placed in anhydrous ethanol for ultrasonic cleaning in turn to remove surface dirt, and then the samples were placed in distilled water for ultrasonic cleaning again to ensure that the sample surface was clean. After cleaning, the sample preparation was completed. Mechanical tensile tests were performed on samples A, A-1, and A-2, respectively, and the two ends of the samples were stretched in opposite directions to the predetermined tensile strain (A: 15%, A-1: 20%, A-2: 25%), and the tensile strain was recorded, and the stretched state was maintained for a period of time.
[0048] Step 1: Use an optical microscope to observe the side of the sample corresponding to the upper surface of the shed, observe the surface crack morphology of the sample, and record the picture.
[0049] Step 2: Use grayscale Figure 2 The recorded images are processed by binary image processing, and the total length L of cracks, the width d between cracks, and the irregularity s of cracks are calculated based on the binary image.
[0050] Step 3: According to the surface crack characteristics (L, d, s) of the sample under different tensile strains and the corresponding weight coefficients ( ω s : 0.20; ω L : 0.6; ω d : 0.2), calculate the aging degree index IR.
[0051] Step 4: The aging degree is proportional to the aging degree index IR. According to the calculated aging degree index IR, the aging degree of the composite insulator shed material is evaluated.
[0052] The tensile strain in this embodiment is 15%, 20%, and 25%, the stretching time is 24 hours, the test temperature is 150°C, and the correction factor is x n The values are: x n =a n .
[0053] The test results of this specific embodiment are shown in Table 1 below.
[0054] Table 1
[0055] The aging index IR of the shed of a composite insulator that has been in service for 6 years is 0.50.
[0056] Example 2 Silicone rubber material was obtained from the shed of a composite insulator that had been in service for 8 years. The shed was selected from the high-voltage end shed, and three dumbbell-shaped samples were prepared (the surface of the sample included the upper surface of the shed), and the sample names were B, B-1, and B-2. The dumbbell-shaped samples were placed in anhydrous ethanol for ultrasonic cleaning in turn to remove surface dirt, and then the samples were placed in distilled water for ultrasonic cleaning again to ensure that the sample surface was clean. After cleaning, the sample preparation was completed. Mechanical tensile tests were performed on samples B, B-1, and B-2, respectively, and the two ends of the samples were stretched in opposite directions to the predetermined tensile strain (B: 15%, B-1: 20%, B-2: 25%), and the tensile strain was recorded, and the stretched state was maintained for a period of time.
[0057] Step 1: Use an optical microscope to observe the side of the sample corresponding to the upper surface of the shed, observe the surface crack morphology of the sample, and record the picture.
[0058] Step 2: Use grayscale Figure 2 The recorded images are processed by binary image processing, and the total length L of cracks, the width d between cracks, and the irregularity s of cracks are calculated based on the binary image.
[0059] Step 3: According to the surface crack characteristics (L, d, s) of the sample under different tensile strains and the corresponding weight coefficients ( ω s : 0.20; ω L : 0.6; ω d :0.2), calculate the aging degree index IR.
[0060] Step 4: The aging degree is proportional to the aging degree index IR. According to the calculated aging degree index IR, the aging degree of the composite insulator shed material is evaluated.
[0061] The tensile strain in this embodiment is 15%, 20%, and 25%, the stretching time is 24 hours, the test temperature is 150°C, and the correction factor is x n The values are: x n =a n .
[0062] The test results of this specific embodiment are shown in Table 2 below.
[0063] Table 2
[0064] The aging degree of the composite insulator shed material is proportional to the aging degree index IR. In the first group of embodiments, IR is 0.50, and in the second group of embodiments, IR is 0.34. Therefore, the aging degree of sample A is higher than that of sample B.
[0065] In summary, by measuring and analyzing the total length of cracks, the width between cracks, and the specific characteristics of the irregularity of cracks, this method can provide more detailed and accurate information on the degree of aging, and can perform a refined evaluation of the degree of aging. This characterization method focuses on the surface structural characteristics of the shed material itself, namely the cracks, and is therefore not affected by the surface cleanliness of the material. The tensile test can simulate the mechanical stress that the material is subjected to during service and promote the evolution of cracks. The strain generated during stretching can promote the evolution of cracks, so that the degree of aging of the shed material can be characterized by changes in crack characteristics.
[0066] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking, characterized in that: include: Collect the surface crack characteristics of the sample under different tensile strains; Calculate the aging index based on the collected surface crack characteristics; The aging degree of the composite insulator shed material is judged based on the aging degree index.
2. The method for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking according to claim 1 is characterized in that: The surface crack characteristics include the total length of the cracks, the width between the cracks, and the irregularity of the cracks; The total length of cracks refers to the total length of all cracks within a certain field of view; the width between cracks refers to the width between adjacent cracks; and the irregularity of cracks refers to the degree to which cracks deviate from a straight line.
3. The method for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking according to claim 1 is characterized in that: The specific process of collecting the surface crack characteristics of the sample under different tensile strains is as follows: Observe the surface crack morphology of the sample under different tensile strains and record pictures; The image is processed by grayscale binarization. The total number of pixels of cracks within a certain field of view is counted based on binarization to obtain the total length L of the cracks. The width is calculated by the ratio of a fixed straight-line distance and the number of cracks intersecting within a fixed straight-line distance. The average value of multiple calculations is taken to obtain the width d between cracks. The irregularity s of the cracks is calculated by the ratio of the total length of a single crack within a fixed straight-line distance to the straight-line distance, and the surface crack characteristics of the samples to be tested under different tensile strains are collected.
4. The method for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking according to claim 1 is characterized in that: The calculation formula for calculating the aging degree index based on the collected surface crack characteristics is as follows: ; Among them, IR is the aging degree index; I (n+1)~n is the index of crack degree variation; L is the total length of cracks; d is the width between cracks; s is the irregularity of cracks; ω s The weight coefficient of the irregularity of the crack is 0.10~0.70; ω L is the weight coefficient of the total length of the crack, ranging from 0.4 to 0.95; ω d is the weight coefficient of the crack width, ranging from 0.15 to 0.80; n is the nth tensile test, n+1 is the n+1th tensile test, and the strain of the n+1th tensile test needs to be greater than the strain of the nth tensile test; m is the number of tensile tests, and m should be greater than or equal to 2; a n is the strain of the nth tensile test; x n is the correction coefficient corresponding to the strain of the nth tensile test.
5. The method for characterizing the aging degree of composite insulator shed materials based on the degree of surface cracking according to claim 1 is characterized in that: The aging degree index is proportional to the change in the surface crack characteristics under different tensile strain amounts, and the aging degree is proportional to the aging degree index; Among them, the changes in surface crack characteristics include the changes in the total length of the cracks, the changes in the irregularity of the cracks, and the changes in the width between the cracks.
6. A composite insulator shed material aging degree characterization system based on surface cracking degree, characterized in that: include: A collection module, used to collect surface crack characteristics of the sample under different tensile strains; A calculation module, used to calculate an aging degree index based on the collected surface crack characteristics; The judgment module is used to judge the aging degree of the composite insulator shed material based on the aging degree index.
7. The composite insulator shed material aging degree characterization system based on surface cracking degree according to claim 6 is characterized in that: The surface crack features in the acquisition module include the total length of the cracks, the width between the cracks, and the irregularity of the cracks; The total length of cracks refers to the total length of all cracks within a certain field of view; the width between cracks refers to the width between adjacent cracks; and the irregularity of cracks refers to the degree to which cracks deviate from a straight line.
8. The composite insulator shed material aging degree characterization system based on surface cracking degree according to claim 6 is characterized in that: The acquisition module is specifically used to acquire the surface crack characteristics of the sample to be tested under different tensile strain amounts in the following manner: Observe the surface crack morphology of the sample under different tensile strains and record pictures; The image is processed by grayscale binarization. The total number of pixels of cracks within a certain field of view is counted based on binarization to obtain the total length L of the cracks. The width is calculated by the ratio of a fixed straight-line distance and the number of cracks intersecting within a fixed straight-line distance. The average value of multiple calculations is taken to obtain the width d between cracks. The irregularity s of the cracks is calculated by the ratio of the total length of a single crack within a fixed straight-line distance to the straight-line distance, and the surface crack characteristics of the samples to be tested under different tensile strains are collected.
9. The composite insulator shed material aging degree characterization system based on surface cracking degree according to claim 6, characterized in that: The calculation module is specifically used to calculate the aging degree index according to the collected surface crack characteristics in the following manner: ; Among them, IR is the aging degree index; I (n+1)~n is the index of crack degree variation; L is the total length of cracks; d is the width between cracks; s is the irregularity of cracks; ω s The weight coefficient of the irregularity of the crack is 0.10~0.70; ω L is the weight coefficient of the total length of the crack, ranging from 0.4 to 0.95; ω d is the weight coefficient of the crack width, ranging from 0.15 to 0.80; n is the nth tensile test, n+1 is the n+1th tensile test, and the strain of the n+1th tensile test needs to be greater than the strain of the nth tensile test; m is the number of tensile tests, and m should be greater than or equal to 2; a n is the strain of the nth tensile test; x n is the correction coefficient corresponding to the strain of the nth tensile test.
10. The composite insulator shed material aging degree characterization system based on surface cracking degree according to claim 6, characterized in that: The aging degree index configured in the judgment module is proportional to the change in surface crack characteristics under different tensile strain amounts, and the aging degree is proportional to the aging degree index; wherein the change in surface crack characteristics includes the change in the total length of cracks, the change in the irregularity of cracks, and the change in the width between cracks.